The Embodied Experience of Microaggressions: Implications for Clinical Practice. Issue 3 (2nd July 2018) - Johnson, Rae; Leighton, Lucia; Caldwell, Christine
Abstract : Ongoing scholarship in multicultural counseling practice has established the significance of microaggressions in the lived experience of clients and in the client–counselor dyad. Grounded in new research into the embodied experience of oppression, this article reviews key concepts in nonverbal communication and traumatology to illustrate how the body is implicated in the transmission of microaggressions and how counselors can become more attentive, informed, and responsive to how social power differences manifest in the body. Las investigaciones actuales sobre la práctica de la consejería multicultural han establecido la importancia de las microagresiones en la experiencia vital de los clientes y en la díada cliente–consejero. Fundamentado en nuevas investigaciones sobre la experiencia corporal de la opresión, este artículo revisa conceptos clave de la comunicación no verbal y la traumatología para ilustrar cómo el cuerpo está involucrado en la transmisión de microagresiones y cómo los consejeros pueden tornarse más atentos, informados y sensibles a cómo las diferencias de poder social se manifiestan en el cuerpo.